The Importance Increasing Attendance Efficiency Accuracy with Presence System in Era Industrial Revolution 4.0 - Tri Hartono; Bintang Nandana Henry; Sirje Nurm; Lukita Pasha; Dwi Julianingsih (International Institute for Advanced Science & Technology (IIAST), 2024)
Employee attendance management systems have become a major focus of the Industrial Revolution 4.0 era due to their significant role in increasing organizational productivity and performance. This study demonstrates the importance of the SmartPLS methodology in analyzing the impact of IoT based attendance technology and big data analytics on the efficiency and accuracy of employee attendance. Both the assessments reviewed show that the use of IoT based attendance technology and the implementation of big data analytics systems have a significant positive impact on the efficiency and accuracy of employee attendance. IoT based attendance technology enables real-time attendance data collection with high accuracy, while big data analytics enables organizations to derive valuable insights from the large volume of collected attendance data. These findings provide a better understanding of the contribution of technology in increasing organizational productivity and performance in today digital age. This study provides valuable insights for business professionals and academics to develop adaptive and effective attendance management strategies. Using IoT based attendance technology and big data analytics, organizations can improve operational efficiency, increase payroll accuracy, and optimize overall human resource utilization. Furthermore, the study also highlights the importance of adapting and innovating in the face of technological developments. By incorporating knowledge of the latest technology and industry trends, organizations can continuously enhance their attendance management strategies to remain relevant and competitive in the ever changing business environment.